Association between KRAS gene polymorphisms and genetic susceptibility to breast cancer in a Chinese population. Issue 1 (12th December 2022) - Jin, Min; Lu, Fengke; Li, Xi; Zhou, Wei; Li, Sihui; Jiang, Yanting; Wu, Huiling; Wang, Jian
Abstract: Objective: The KRAS gene has a pathophysiological role in the development of many cancers. This study aims to investigate the relationship between KRAS polymorphisms and genetic susceptibility to breast cancer. Method: The rs712, rs12587 and rs9266 gene loci in the KRAS gene of 421 subjects (141 breast cancer patients, 141 benign breast tumours and 139 healthy controls) were analysed by the polymerase chain reaction and SNaPshot sequencing. Transcriptomic information on KRAS and corresponding clinical information was downloaded from the TCGA and GTEx databases. Differences in KRAS expression between breast cancer tissues and control tissues were analysed. Results: We found no significant association between KRAS rs712 and rs12587 locus gene polymorphisms and an increased risk of developing benign breast tumours and breast cancer ( p  > 0.05). The KRAS rs9266 locus mutation heterozygous model CT and dominant model CT + TT were significantly associated with an increased risk of breast cancer (both p  < 0.05). In addition, the TAT haplotype was expressed at an increased frequency, and the GAC haplotype was expressed at a reduced frequency in breast cancer compared with controls (both p  < 0.05). We found that KRAS was over expressed in breast cancer tumour tissues compared with the control tissues ( p  < 0.0001). Conclusion: The KRAS rs9266 gene polymorphism and the TAT haplotype may be associated with an increased risk of breast cancer in Chinese women. The GAC haplotype may be a protective factor against breast cancer. Abstract : The KRAS gene polymorphism may be associated with an increased risk of breast cancer in Chinese women.